Design of a low-cost wireless surface EMG acquisition system - Jianting Fu; Jian Chen; Yizhi Shi; Yao Li (2013 6th International IEEE/EMBS Conference on Neural Engineering (NER), 2013)
A low-cost wireless surface EMG acquisition system has been designed for general purpose human-machine interaction. The system includes disposable surface EMG sensor, wireless communication module and signal analysis unit. The system has four simultaneous recording channels with the resolution of micro volt and wireless communication distance ranges 15 meters. A new pattern extraction algorithm has been developed to predict hand wrist gesture from forearm-surface EMG signal. This EMG data acquisition system provides a convenient human-machine interaction interface for biomimetic control applications.